The Association Between Emotion Regulation, Physiological Arousal, and Performance in Math Anxiety - Pizzie, Rachel G.; Kraemer, David J. M. (Frontiers in Psychology, 2021)
Emotion regulation (ER) strategies may reduce the negative relationship between math anxiety and mathematics accuracy, but different strategies may differ in their effectiveness. We recorded electrodermal activity (EDA) to examine the effect of physiological arousal on performance during different applied ER strategies. We explored how ER strategies might affect the decreases in accuracy attributed to physiological arousal in high math anxious (HMA) individuals. Participants were instructed to use cognitive reappraisal (CR), expressive suppression (ES), or a “business as usual” strategy. During the ES condition, HMA individuals showed decreases in math accuracy associated with increased EDA, compared to low math anxious (LMA) individuals. For both HMA and LMA groups, CR reduced the association between physiological arousal and math accuracy, such that even elevated physiological arousal levels no longer had a negative association with math accuracy. These results show that CR provides a promising technique for ameliorating the negative relationship between math anxiety and math accuracy.